The impact of war in Ukraine on EU migration - Guild, Elspeth; Groenendijk, Kees (Frontiers in Human Dynamics, 2023)
When the Russian Federation invaded Ukraine on 24 February 2022, one of the most immediate and dramatic reactions of the European Union (EU) was to open a special protection scheme for Ukrainians and non-Ukrainians who were resident in the country on the date of the invasion to enter the EU and remain with extensive rights. (All EU states are part of the scheme with the exception of Denmark which because of particularities in its constitutional position in the EU opened a parallel national scheme rather than join the EU scheme). The legal basis of the scheme is a directive adopted in 2001, on Temporary Protection which had been slated for repeal but which had not yet occurred at the date of the invasion and is now on hold. Since then, according to UNHCR, 8,046,560 Ukrainians (or persons who were resident in Ukraine at the relevant date) have been recorded across Europe. In this article we examine the status and rights of TP beneficiaries in the EU and the challenges ahead for them and the EU as the war continues.